SEA-LEVEL VARIABILITY IN THE JAVA SEA LINKED TO MONSOON FORCING AND CLIMATE TELECONNECTIONS (2009–2024) - Nugraheni, Imma Redha; Lestari, Tri Anggun; Kristianto, Aries; Avrionesti, Avrionesti; Rejeki, Hasti Amrih; Wijaya, Yusuf Jati (Indonesian Physical Review, 2025)
The Java Sea is a shallow, strait-connected shelf where seasonal monsoon forcing and climate modes can strongly modulate sea level, yet their sectoral expressions remain under-resolved. Altimetric observations from 2009–2024 (DUACS) are analyzed and validated against a network of Indonesian tide gauges and partition the basin into western (W-JS), central (C-JS), and eastern (E-JS) sectors. After detrending, the seasonal cycle is diagnosed via amplitude and phase metrics and quantifies interannual teleconnections using lead–lag cross-correlations (−12 to +12 months) between sea-level anomaly (SLA) and the Dipole Mode Index (DMI) and Southern Oscillation Index (SOI), with confidence intervals. DUACS reproduces tide-gauge variability with high skill (median correlation ≈ 0.82; RMSE 5–11 cm; small negative biases), supporting its use as a basin proxy. Seasonally, SLA peaks in DJF, weakens in MAM, reaches a pronounced minimum in JJA, and recovers in SON, with marked zonal heterogeneity: E-JS exhibits the strongest annual range (~18 cm) versus W-/C-JS (~12–13 cm). The seasonal phase is non-synchronous (W-JS maxima in May–June; E-JS in December–January), while C-JS behaves as a transition zone. Interannually, IOD impacts are near-synchronous and negative (lag-0, r ~ −0.41 to −0.47 across sectors), whereas ENSO peaks at short positive lags (SOI leads by ~1 month; r ~ 0.45–0.53), implying higher sea level during La Niña and lower during El Niño. These sign-and-lag relationships, combined with tide and surge information, have the potential to inform seasonal outlooks for ports and low-lying coastal areas of Java.